Studi Literatur Perjanjian Investasi Smelter Nikel Indonesia-China: Peluang dan Tantangan Transfer Teknologi - Holga Holga; Muhammad Zidan Hasan; Grace Evelina Buji; Rinto Alexandro (Edunomics Journal, 2026)
Indonesia’s nickel downstreaming policy has accelerated rapidly through large-scale investment from China, positioning the country as a key player in the global supply chain for electric vehicle batteries. While these investments have expanded smelter capacity and boosted exports, their contribution to technology transfer remains limited. This study employs a systematic literature review (SLR) to analyze Indonesia–China investment agreements in the nickel smelter sector and evaluate their implications for technological upgrading. Drawing on the Eclectic Paradigm, absorptive capacity, and linkage development theories, the review finds that technology transfer is mostly operational, with core metallurgical technologies still dominated by Chinese firms. Weak research infrastructure, limited human capital, and the absence of binding technology-sharing clauses hinder Indonesia’s capacity to internalize foreign knowledge. Although economic benefits are substantial, technological spillovers are low. Strengthening regulatory frameworks, improving vocational training, and enhancing research collaboration are essential to achieve sustainable and strategic technological development